2017
DOI: 10.1186/s12916-017-0812-x
|View full text |Cite
|
Sign up to set email alerts
|

Food for thought: why does the medical community struggle with research about nutritional therapy in the acute care setting?

Abstract: Although clinical nutrition is a frequently used intervention in inpatient care, high quality trials proving its effectiveness and safety when used in the acutely-ill polymorbid medical inpatient population are largely lacking. From an evolutionary perspective, illness-related low appetite is protective and part of the host response to improve recovery from disease. Large and well performed trials in the intensive care setting have shown deleterious effects of (parenteral) feeding strategies aiming at higher c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Previous studies have found that inflammation because of acute or chronic disease causes metabolic changes by influencing different pathways. 21,22 Inflammation has effects on appetite and food intake, gastrointestinal functioning of the stomach and gut, and, on a cellular level, on insulin resistance, among others. 23 Among other mechanisms, these effects are mediated by circulating cytokines released as part of the systemic inflammatory response.…”
Section: Control Interventionmentioning
confidence: 99%
“…Previous studies have found that inflammation because of acute or chronic disease causes metabolic changes by influencing different pathways. 21,22 Inflammation has effects on appetite and food intake, gastrointestinal functioning of the stomach and gut, and, on a cellular level, on insulin resistance, among others. 23 Among other mechanisms, these effects are mediated by circulating cytokines released as part of the systemic inflammatory response.…”
Section: Control Interventionmentioning
confidence: 99%
“…Trotz methodischer Herausforderungen aufgrund der heterogenen Patientenpopulation und dem Fehlen von großen Interventionsstudien [24,25], ist es der Arbeitsgruppe gelungen, evidenzbasierte Empfehlungen zur nichtkrankheitsspezifischen Ernährungstherapie bei polymorbiden Patienten zu erarbeiten. Als Resultat sind 22 praktische Empfehlungen und 4 Stellungnahmen entstanden, welche im klinischen Alltag im Umgang mit mangelernährten, hospitalisierten, polymorbiden Patienten genutzt werden können.…”
Section: Schlussfolgerung/ausblickunclassified
“…Zusammenfassend lässt sich sagen, dass bei internistischen, hospitalisierten Patienten ein hohes Mangelernährungsrisiko besteht und durch eine Ernährungstherapie wahrscheinlich ein Gewinn hinsichtlich niedriger Rehospitalisationsrate und Hospitalisationsdauer sowie vielleicht der Mortalität erreicht werden kann [10]. Die Qualität der heutigen Evidenz ist aber noch zu schwach und es braucht weitere groß angelegte Studien in diesem Bereich [12], dies auch um mögliche Risiken der Ernährung wie das "Refeeding-Syndrom" oder "Overfeeding" auszuschließen [13 -15].…”
Section: Introductionunclassified